Tiered Reading Program: A Case Study in Grade Two of A Private Elementary School in Central Java - Meri Fuji Siahaan; Anggun Clarissa Saragih (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
Developing students’ reading skills is highly required to be taught to the students from their young age since it affects the students’ achievement in learning . One of the private elementary schools in Central Java has been implementing a reading program called “tiered reading” for almost a year. The purpose of this study was to explore the implementation of the tiered reading program in grade two in one of the private elementary schools in Central Java. Four teachers who taught in four different paralel classes were the participants of this research. This case study utilized teachers interviews, classroom observations during the implementation of tiered reading program and documents collections such as worksheets and story books the teachers used. The data were analyzed by coding, categorizing and developing themes. The data analysis revealed three important themes; contradictory meaning between the teachers’ concept understanding and the teachers’ teaching strategies in the classroom. Reading for fluency and for remembering are the other emerging themes. The research concluded that the implementation of tiered reading was oriented to mechanical reading skill and literal comprehension reading